Manajemen Tenaga Pendidik dalam Meningkatkan Mutu Pendidikan Siswa Tunagrahita - Satria Budi, M. Hanif (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This thesis is the result of research that presents the potential for teaching staff management in improving the quality of education for mentally retarded students at SLB C Dharma Wanita Pare. The purpose of this research is to determine the management of teaching staff at SLB C Dharma Wanita Pare which includes planning, implementation, evaluation as well as supporting and inhibiting factors in improving the quality of education. The research method used is descriptive qualitative, namely research that is oriented towards natural phenomena based on what occurs in the field and the approach used in this research is a case study. The results of this research show that: 1) Planning the management of teaching staff, namely by conducting a job analysis regarding the form of work, duties and positions to ensure that students' educational needs are met, 2) Implementation of teaching staff management is carried out through several processes, namely recruitment, selection, job placement, compensation, training and development, and dismissal of teaching staff, all of which went well because a thorough planning process had previously been carried out by the school principal, 3) Evaluation of the management of teaching staff was carried out in the form of supervision to measure the extent of effectiveness the work of teaching staff in meeting the needs of students. 4) Supporting and inhibiting factors greatly influence the success of the teaching staff management process, both from the school principal, the competence of teaching staff, facilities and infrastructure, financing, as well as the participation of parents and the school committee. The practical implications of the results of this research are that it is intended for educational institutions with a similar culture, namely schools with students with special needs only, whereas for educational institutions in general it is certainly very different, considering the learning environment is with ordinary regular students, so there are no specialties that must be had. by educators.